Beyond body mass index: the role of fat distribution in male sperm quality - Ma, Dongsheng; Zhang, Mengru; Zhang, Xiaoguang; Xu, Lizhen (Frontiers in Endocrinology, 2025)
ObjectiveTo explore the dual role of obesity and fat distribution on sperm dynamics and morphological parameters and to further assess the impact on male fertility.MethodsA population of 823 male semen examinations from the Male Reproductive Health Database (FAST-Date, 2022-2025), was retrospectively analyzed for general information, obesity indicators, sperm dynamics and morphology parameter ratings, and male fertility assessment indicators.ResultsThere were differences in sperm dynamics and sperm morphology parameters between the non-obesity and obesity group populations (P < 0.05), which were shown to be poorer in both sperm dynamics parameters in the obesity group population as compared to the non-obesity group population, and morphological parameters. There were differences in total sperm count, sperm concentration, sperm dynamics parameters and sperm morphology parameters among obesity subgroups, and central obesity showed that sperm dynamics and morphology parameters were better than those of generalized obesity and simple obesity groups. And obesity group had higher sperm DFI compared to non-obesity group (23.83 ± 12.25 vs. 14.16 ± 9.80), whereas there was no statistically significant difference in sperm DFI between obesity subgroups (P = 0.210). Multivariate regression analysis showed that PR was significantly negatively associated with the risk of male infertility (adjusted OR, 0.93; 95% CI, 0.89-0.98; P = 0.004). hyperactivated spermatozoa revealed significant associations with the adverse pregnancy outcomes (adjusted OR, 0.93; 95% CI, 0.87–1.00; P = 0.049). A significant direct effect of obesity on sperm DFI was observed (β= -9.67, 95% CI: -11.19~-8.15, P < 0.001), while DFI itself was a significant predictor of adverse pregnancy outcomes (β=-0.02, 95% CI: -0.04~-0.01, P = 0.029).ConclusionObesity reduces sperm quality (sperm dynamics and morphological parameters), whereas central obesity outperforms generalized and simple obesity in some sperm dynamics and morphological parameters. This underscores the clinical importance of assessing fat distribution, not just overall obesity, in the evaluation of male reproductive health.